Comparative DNA methylation analysis to decipher common and cell type-specific patterns among multiple cell types. (23rd April 2016) - Yang, Xiaofei; Shao, Xiaojian; Gao, Lin; Zhang, Shihua
Abstract : DNA methylation has been proved to play important roles in cell development and complex diseases through comparative studies of DNA methylation profiles across different tissues and samples. Current studies indicate that the regulation of DNA methylation to gene expression depends on the genomic locations of CpGs. Common DNA methylation patterns shared across different cell types and tissues are abundant, and they are likely involved in the basic functions of cell development, such as housekeeping functions. By way of contrast, cell type-specific DNA methylation patterns show distinct functional relevance with cell type specificity. Additionally, abnormal DNA methylation patterns are extensively involved in tumour development. Pan-cancer methylation patterns reveal common mechanisms and new similarities of different cancers, while cancer-specific patterns are relating to tumour heterogeneity and patient survival. Moreover, DNA methylation patterns in specific cancer are relevant with diverse regulatory elements such as enhancers and long non-coding RNAs. In this review, we survey the recent advances on DNA methylation patterns in normal or tumour states to illustrate their potential roles in cell development and cell canceration.